Enhanced Neutrophil Extracellular Trap Formation in Acute Pancreatitis Contributes to Disease Severity and Is Reduced by Chloroquine - Murthy, Pranav; Singhi, Aatur D.; Ross, Mark A.; Loughran, Patricia; Paragomi, Pedram; Papachristou, Georgios I.; Whitcomb, David C.; Zureikat, Amer H.; Lotze, Michael T.; Zeh III, Herbert J.; Boone, Brian A. (Frontiers in Immunology, 2019)
Background: Neutrophil extracellular traps (NETs) are generated when activated neutrophils, driven by PAD4, release their DNA, histones, HMGB1, and other intracellular granule components. NETs play a role in acute pancreatitis, worsening pancreatic inflammation and promoting pancreatic duct obstruction. The autophagy inhibitor chloroquine (CQ) inhibits NET formation; therefore, we investigated the impact of CQ mediated NET inhibition in murine models of pancreatitis and human correlative studies. Methods: L-arginine and choline deficient ethionine supplemented (CDE) diet models of acute pancreatitis were studied in wild type and PAD4-/- mice, incapable of forming NETs. Isolated neutrophils were stimulated to induce NET formation and visualized with fluorescence microscopy. CQ treatment (0.5 mg/ml PO) was initiated after induction of pancreatitis. Biomarkers of NET formation, including cell-free DNA, citrullinated histone H3 (CitH3), and MPO-DNA conjugates were measured in murine serum and correlative human patient serum samples. Results: We first confirmed the role of NETs in the pathophysiology of acute pancreatitis by demonstrating that PAD4-/- mice had decreased pancreatitis severity and improved survival compared to wild-type controls. Furthermore, patients with severe acute pancreatitis had elevated levels of cell-free DNA and MPO-DNA conjugates, consistent with NET formation. Neutrophils from mice with pancreatitis were more prone to NET formation and CQ decreased this propensity to form NETs. CQ significantly reduced serum cell-free DNA and citrullinated histone H3 in murine models of pancreatitis, increasing survival in both models. Conclusions: Inhibition of NETs with CQ decreases the severity of acute pancreatitis and improves survival. Translating these findings into clinical trials of acute pancreatitis is warranted.